Prognostic value of the immunological phenomena and relationship with clinicopathological characteristics of the tumor — the expression of the early CD69+, CD71+and the late CD25+, CD26+, HLA/DR + activation markers on T CD4+ and CD8+ lymphocytes in squamous cell laryngeal carcinoma. Part II - Przemysław Lewkowicz; Magdalena Bryś; Iwona Lewy-Trenda; Andrzej Kulig; Ewa Głowacka; Katarzyna Starska (Folia Histochemica et Cytobiologica, 2012)
One of the most important challenges in contemporary oncology is to find objective biomarkers of tumor aggressiveness, which help to identify more invasive phenotypes of the carcinoma. The purpose of this study was to investigate the relationships between the early and the late activation markers expression on T CD4+ and CD8+ cells subpopulations and certain clinicopathological characteristics of the neoplastic infiltration in order to determine their role as biomarkers for tumor behavior in squamous cell laryngeal carcinoma. Analysis of the early (CD69+, CD71+) and the late activation antigens (CD25+ high, CD26+, HLA/DR+) expression on T CD4+ and CD8+ lymphocytes by cytofluorymetry in 55 patients treated for squamous cell laryngeal carcinoma was performed. Clinicomorphological analysis on the basis of TNM criteria and tumor front grading, which included tumor-related features and adjacent stroma-related characteristics of the peripheral edge of infiltration was carried out. The relationships between the activation markers expression and parameters of tumor aggressiveness were investigated. Our work revealed statistically significant differences in the expression of the studied activation markers on T cells with regard to certain clinicomorphological fetaures. The expressions of CD69+ and CD71+ antigens on T CD3+CD4+ and CD3+CD8+ cells as well as CD4+HLA/DR+ markers were higher for pT3 and pT4 tumors, in comparison with pT2 carcinomas. Moreover, tumors with the smallest number of TFG points were characterized by significantly lower values of the average expression of CD3+CD69+ and CD3+CD71+ as well as CD4+HLA/DR+ markers on T lymphocytes. In addition, more aggressive and deeply infiltrating laryngeal carcinomas were most often characterized by significantly higher values of the average expression of CD69+ and CD71+ antigens on CD8+ as well as HLA/DR+ markers on CD4+. Our study confirmed the implication of the early and the late activation antigens expression on CD4+ and CD8+ T lymphocytes in clinicomorphological parameters of the tumor, especially TFG total score and depth of invasion, and their importance as indicators of the invasive phenotype of laryngeal carcinoma. (Folia Histochemica et Cytobiologica 2011; Vol. 49, No. 4, pp. 593–603)